Exploring university students’ podcasting knowledge and podcast production intention and motivation: a comparative study by gender and age - Mohd Amin, Noraziah; Mohamad Marzaini, Anwar Farhan; Zulkifli, Che Nooryohana; Ab Latif, Nur Afiqah (Universiti Teknologi MARA, Kedah, 2025)
Podcasts provide diverse information, encompassing personal narratives, cultural assessments, and conversations on contemporary issues. Podcast users have been consistently rising, including various age demographics such as university students. Considering the increasing prevalence of podcasts in everyday life, it is essential to investigate whether the younger generation is aware of podcasts and exhibits interest in podcasting. Moreover, the current literature reveals that most research on podcasts has predominantly concentrated on reasons for listening to podcasts rather than general understanding of podcasts and interest in producing their own podcasts. To bridge the gap in the literature, the present study quantitatively investigates local university students’ knowledge about podcasts and their intention as well as motivation to create their own podcasts by using gender and age as elements of comparison.